1998
DOI: 10.1111/j.1749-6632.1998.tb08989.x
|View full text |Cite
|
Sign up to set email alerts
|

The Response of Fungal Propagules to Competitive Energy Stress in Soil

Abstract: 154 ANNALS NEW YORK ACADEMY OF SCIENCES FIGURE 1. Arithmetic plot showing relationship of endogenous 14 C loss from labeled sclerotia of Sclerotium rolfsii to their ability to germinate in nutrient medium (potato-dextrose broth; PDB) or on salts solution containing no nutrients (y = 143.9-2.7x for PDB; y = 111.8-2.4x for the salts solution). Sclerotia of differing 14 C contents were obtained by incubating them in soil for various periods of time. Source: Ref. 10.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…Thus, in Escherichia coli it has been shown that transcription factors recognize specific heat-shock promoters, and that in most bacteria the control of major Heat-Shock genes is highly regulated (Segal and Ron, 1998). In fungi, it has been observed that stress originated from nutrient deprivation causes debilitation of fungal propagules, autolysis, inhibition of spores and loss of pathogenic aggressiveness (Hyakumachi and Arora 1998). This is another common aspect of the stress reaction response, i.e.…”
mentioning
confidence: 99%
“…Thus, in Escherichia coli it has been shown that transcription factors recognize specific heat-shock promoters, and that in most bacteria the control of major Heat-Shock genes is highly regulated (Segal and Ron, 1998). In fungi, it has been observed that stress originated from nutrient deprivation causes debilitation of fungal propagules, autolysis, inhibition of spores and loss of pathogenic aggressiveness (Hyakumachi and Arora 1998). This is another common aspect of the stress reaction response, i.e.…”
mentioning
confidence: 99%